URBAN AGRICULTURE AS A FOOD SECURITY STRATEGY FOR URBAN DWELLERS: A CASE STUDY OF MKOBA RESIDENTS IN THE CITY OF GWERU, ZIMBABWE - Chaminuka, Nyasha; Dube, Ernest (PEOPLE: International Journal of Social Sciences, 2017)
Urban agriculture is a common strategy used by urban dwellers in their endeavor to pursue sustainable food security. This article analyzed the practice of urban agriculture by urban dwellers in the city of Gweru in Zimbabwe, with a specific focus on Mkoba suburb. This qualitative study sought as its objectives, to discuss factors that have contributed to the growth of urban agriculture; to analyze how urban agriculture contributes to the well-being of urban dwellers; to examine the legal framework governing urban agriculture in Zimbabwe; and, to ascertain challenges faced by urban farmers in pursuit of urban agriculture.Purposive sampling was used and data were gathered from 26 participants through interviews and focus group discussions.The findings were that the growth of urban agriculture is influenced by rapid population growth, high levels of poverty, high food prices, and high rate of unemployment. The study further found that urban agriculture promotes food security, provides employment and encourages savings. The Urban Councils Act Chapter 29:15; Regional Town Planning Act Chapter 29:12; Environmental Management Act Chapter 20:27; Public Health Act Chapter 15:09; Forestry Act Chapter 19:05; and, the Diary Act Chapter 18:08, all have a bearing on urban agriculture. These Acts do not support, but impede the practice of urban agriculture. There are also challenges that impede the practice of urban agriculture, including the absence of supportive legislation, lack of support from central and local governments, and lack of funding.The study concluded that urban agriculture is an important practice that cannot be dispensed with, as strengthens food security of urban dwellers. The study recommends enactment of supportive legislation, provision of small grants to urban farmers, and creation of farmers associations. Future research should focus on ways of improving the livelihoods of urban farmers. Urban farmers and key stakeholders are largely expected to benefit from the study.